2015
DOI: 10.1007/s13277-015-3873-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human 67-kDa laminin receptor sensitizes multidrug resistance colon cancer cell line SW480 for apoptosis induction

Abstract: The adhesion mediated drug resistance in cancer cells resulted from adhesion of the extracellular matrix is a major cause for multidrug resistance (MDR) and leads chemotherapeutic failure for colon cancer. In this study, we explored the role of 67-kDa laminin receptor (67LR) in chemotherapeutic drug resistance in colon cancer cells. SiRNA-mediated knockdown of 67LR decreased the cell adhesion when laminins were applied. Moreover, 67LR knockdown increased the expression of pro-apoptotic gene Bax but inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Although 67LR has been well studied in various tumour cells 20,21 , few studies on its expression in the kidney have been conducted. In this study, we found that 67LR was expressed in the epithelial cells of the proximal tubules, the epithelial cells of the renal capsules, podocytes, vascular endothelial cells, and fibroblasts in the kidney.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although 67LR has been well studied in various tumour cells 20,21 , few studies on its expression in the kidney have been conducted. In this study, we found that 67LR was expressed in the epithelial cells of the proximal tubules, the epithelial cells of the renal capsules, podocytes, vascular endothelial cells, and fibroblasts in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in 67LR expression might have been due to the role of 67LR in the pathology of renal injury. 67LR is reported to be a molecular marker of metastatic aggressiveness 20,21 . Renal epithelial cells could be transformed to the mesenchymal cell phenotype and acquire the ability to migrate and invade, which could promote the development of renal fibrosis 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S4). The apoptotic induction observed is suggested to be due to the reduced interaction of LRP/LR with focal adhesion kinase (FAK) [52,56]. In particular, a study performed by Lu et al (2016) demonstrated that siRNA-mediated knock-down of LRP/LR reduced FAK phosphorylation, leading to the knock-down of the anti-apoptotic protein Bcl-2 and an up-regulation of the pro-apoptotic Bax protein, reiterating that the knock-down of LRP/LR induces apoptosis [56].…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic induction observed is suggested to be due to the reduced interaction of LRP/LR with focal adhesion kinase (FAK) [52,56]. In particular, a study performed by Lu et al (2016) demonstrated that siRNA-mediated knock-down of LRP/LR reduced FAK phosphorylation, leading to the knock-down of the anti-apoptotic protein Bcl-2 and an up-regulation of the pro-apoptotic Bax protein, reiterating that the knock-down of LRP/LR induces apoptosis [56]. Moreover, another study performed by Sun et al (2014) showed that the LRP/LR-laminin-1 interaction may allow for LRP/LR's interaction with FAK, leading to the activation of the PI3-kinase/AKT and MEK/ERK 1/2 cellular survival pathways as well as an increased expression of the Bcl-2 protein [52].…”
Section: Discussionmentioning
confidence: 99%